The First Case of Candida auris Detection and Infection Control in a Pediatric Bone Marrow Transplant Child Patient in Guangxi, China - Yang L; Hong K; Luo J; Wang L; Zhang L; Jiang L; Peng Q; Guo J (Infection and Drug Resistance)
Liu Yang,1,* Kaiting Hong,2,* Jiajia Luo,1,* Lili Wang,2 Lei Zhang,1 Lijun Jiang,1 Qiliu Peng,1 Jian Guo3 1Department of Clinical Laboratory, Guangxi International Zhuang Medicine Hospital, Nanning, Guangxi, People’s Republic of China; 2Department of Laboratory Medicine, Zhoushan Women and Children Hospital, Zhoushan, People’s Republic of China; 3Department of Laboratory Medicine, Shanghai East Hospital, School of Life Sciences and Technology, Tongji University, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jian Guo; Qiliu Peng, Email guojian1110@126.com; pengql45@163.comAbstract: Candida auris is an emerging yeast species and an opportunistic pathogen. Due to its multi-drug resistance and ability to colonize and transmit, it poses a significant risk for outbreaks in medical institutions. In this study, we report the first case of C. auris detected in a pediatric bone marrow transplant child patient in Guangxi, China. C. auris was isolated from urine and identified using matrix-assisted laser desorption ionization–time of flight (MALDI-TOF) mass spectrometry, and the isolate belonged to clade I using sequencing. We have implemented stringent infection control measures including personal protective equipment and treatment in a single room, and conducted regular surveillance screening of patients’ body surfaces, as well as those of related medical and logistics personnel, medical equipment, and surrounding environmental surfaces. These measures aim to effectively control the colonization of C. auris in patients, prevent its spread within hospitals, and ensure the quality of diagnosis and treatment for patients.Keywords: Candida auris, colonization, MALDI-TOF, infection control, surveillance screening